2015
DOI: 10.1021/jacs.5b01705
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Arylative Dearomatization of Indoles via Pd-Catalyzed Intramolecular Reductive Heck Reactions

Abstract: A highly enantioselective intramolecular arylative dearomatization of indoles via palladium-catalyzed reductive Heck reactions was developed. The new strategy led to a series of optically active indolines bearing C2-quaternary stereocenters in modest to good yields with excellent enantioselectivities (up to 99% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
90
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(93 citation statements)
references
References 50 publications
0
90
1
2
Order By: Relevance
“…It was proposed that the addition of trialkylammonium salts in ethylene glycol facilitates the halide dissociation through its hydrogen bond donor capacity. Another enantioselective transformation of this class was reported with the asymmetric arylative dearomatization of indoles through palladium‐phosphine‐catalyzed reductive Heck reaction using sodium formate in methanol . To date, the asymmetric reductive Heck reaction is rather limited to intramolecular reactions, which is particularly interesting for the synthesis of natural products .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that the addition of trialkylammonium salts in ethylene glycol facilitates the halide dissociation through its hydrogen bond donor capacity. Another enantioselective transformation of this class was reported with the asymmetric arylative dearomatization of indoles through palladium‐phosphine‐catalyzed reductive Heck reaction using sodium formate in methanol . To date, the asymmetric reductive Heck reaction is rather limited to intramolecular reactions, which is particularly interesting for the synthesis of natural products .…”
Section: Introductionmentioning
confidence: 99%
“…Another enantioselective transformation of this class was reported with the asymmetric arylative dearomatization of indoles through palladium‐phosphine‐catalyzed reductive Heck reaction using sodium formate in methanol . To date, the asymmetric reductive Heck reaction is rather limited to intramolecular reactions, which is particularly interesting for the synthesis of natural products . To the best of our knowledge, there are no examples that describe the “direct intermolecular” enantioselective reductive Heck reaction with a high ee , most likely because of the challenges involved in the asymmetric induction step.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Palladium-catalyzed dearomative Heck arylation of indoles provides ar eliable approach to indolines,w hich are frequently occurring substructures in natural products. [9] Further,t hrough aH eck/benzyl-Pd capture sequence,d iastereoselective indole dearomative difunctionalization reactions were established, as reported by the groups of Lautens and Liang, as well as ourselves.This sequqnce furnishes ar ange of 2,3-disubstituted indolines, bearing vicinal stereocenters,b ya rylcyanation, diarylation, and arylalkynylation reactions. [9] Further,t hrough aH eck/benzyl-Pd capture sequence,d iastereoselective indole dearomative difunctionalization reactions were established, as reported by the groups of Lautens and Liang, as well as ourselves.This sequqnce furnishes ar ange of 2,3-disubstituted indolines, bearing vicinal stereocenters,b ya rylcyanation, diarylation, and arylalkynylation reactions.…”
mentioning
confidence: 85%
“…Subsequent ligand examination revealed that the amino substituent of BINOL-based phosphoramidite ligands significantly influenced the enantioselectivity (entries [5][6][7][8][9][10][11][12][13][14]. Surprisingly,t he addition of CuI (5 mol %) as ac o-catalyst fully suppressed the reaction (entry 2).…”
mentioning
confidence: 99%
“…取代吲哚底物 1 [6] 和芳基炔酸 2 [14] 的合成均采用文 献报道的方法. 138.7, 135.7, 132.8, 132.5, 131.1, 129.1, 128.8, 127.89, 127.87, 126.0, 125.0, 124.6, 123.1, 122.4, 117.6, 87.0, 86.6, 75.3, 43.1, 26.7 8, 149.5, 143.3, 138.9, 135.5, 131.1, 130.2, 129.7, 129.0, 127.9, 126.0, 124.8, 124.4, 123.6, 122.6, 117.6, 86.9, 86.8, 75.0, 43.1, 26.8, 22.0 8, 149.5, 143.3, 138.9, 135.6, 131.2, 130.3, 129.8, 129.0, 127.87, 127.86, 126.0, 124.8, 124.5, 123.6, 122.6, 117.6, 86.9, 86.8, 75.0, 43.2, 26.8, 22 6,166.8,164.8,151.7 (d,J=9.9 Hz),138.7,135.4,131.2,129.2,128.9,128.1 (d,J=12.6 Hz),126.8 (d,J=9.9 Hz),126.1,125.2,122.3,117.6,116.7,116.6,110.7,110.5,87.3,86.2,74.9,43.2,26.7. 8-氟-10b-甲基-11-(苯基乙炔基)-10b,11-二氢-6H-异 160.7, 148.6, 142.3, 140.4, 132.7, 132.2, 131.2, 128.9, 128.8, 128.2, 128.0, 127.9, 127.1, 126.0, 125.0, 124.6, 124.1, 122.5, 111.5, 103.2, 87.5, 87.0, 81.2, 55.7, 44.7 2, 146.0, 143.2, 139.4, 135.5, 132.7, 132.4, 131.2, 129.2, 129.1, 128.0, 127.9, 125.8, 125.3, 124.6, 122.3, 117.5, 110.3, 106.7, 87.7, 85.9, 76.3 6, 149.1, 138.7, 138.0, 135.8, 132.8, 132.4, 131.0, 129.0, 128.7, 128.6, 126.0, 124.9, 124.5, 123.1, 119.4, 117.6, 87.1, 85.9, 75.3, 43.2, 26.7, 21.3 168.3, 149.0, 139.8, 138.5, 136.2, 133.0, 132.6, 131.6, 129.04, 129.02, 128.8, 127.9, 125.9, 125.1, 125.0, 124.7, 123.2, 122.2, 117.6, 90.3, 85.9, 75.1, 43.3, 26.8, 19.9 …”
Section: 基于文献结果 我们提出了如下反应机理(Schemementioning
confidence: 99%